Accuracy of calculated knee joint movements depending on marker sets and leg position - Lindner, F.; Roemer, K.; Milani, T. L. (ISBS - Conference Proceedings Archive (Konstanz), 2008)
This study investigated the influence of different marker sets and different leg positions on time histories of skeletal kinematics of the lower limb. Surface markers were attached to the thigh and the shank to reproduce their kinematics during a knee movement cycle. Certain selections of posture and marker sets minimised the expected measurement errors without further optimisation procedures. However, the results showed an approximation to skeletal movement, only. The results lead to recommendations for the use of skin based marker systems.